Aerosol Number Size Distribution Measurements at Hanle, a Free Tropospheric High-Altitude Site in Western Himalayas - Kompalli, Sobhan Kumar; Sreekanth, V; Chaubey, Jai Prakash; Gogoi, Mukunda M; Babu, S Suresh; Prabhu, Tushar P; Moorthy, K Krishna (Journal of the Institute of Engineering, 2012)
Aerosol characteristics over the high altitude stations, akin to pristine and free conditions are important to understand the background aerosol features against which polluted and urban environments could be compared. In addition it is also important to monitor the changes brought about by the large-scale processes, which result in lofting and transporting of aerosols from different source regions to higher altitude levels. Moreover, these aerosols have a significant role in modifying clouds especially cold clouds. The availability of significant amount of solar UV radiation at these altitudes, along with water vapour and OH, if present, makes these regions conducive for formation of new particles from gas phase reaction products involving precursors of natural or anthropogenic origin. Such processes play a significant role in modulating the size distribution of free tropospheric aerosols and hence their radiative impacts. In this work, aerosol number size distribution measurements carried out from a high altitude free tropospheric Himalayan location, Hanle (32.78°N, 78.96°E, 4530 m amsl) during the period from May through December 2010 are examined. The monthly mean total number concentration (Nt) increased from May (614 ± 188 cm-3) to October (1498 ± 792 cm-3) and decreased slightly through December (1158 ± 470 cm-3). Fine mode aerosols (size < 100nm) contributed mostly to the total number concentration. The fractional contribution of the fine mode aerosols to the total number concentration, showed a clear increasing trend from May (~ 0.57) to December (~ 0.81). The number size distribution, which remained unimodal in May, June months with a mode in accumulation size range (around 100nm), changed to a bimodal distribution subsequently with a mode in the nucleation size range (< 25nm), indicating the possibility of new particle formation. The results are discussed in light of the possible association between the variation of the aerosol number concentration to long-range transport and thermally driven mesoscale processes such as mountain/valley winds. DOI: http://dx.doi.org/10.3126/jie.v8i3.5940 JIE 2011; 8(3): 140-146